Building Robust Pretrained Deep Learning Models for Diabetic Retinopathy (DR) Classification on Local Datasets - ABIABID, Abdelbadie; BEYAT, Ahmed Taha (Université of eloued جامعة الوادي, 2025)
Diabetic Retinopathy is a top cause of bad eye sight all over the world, showing how key it is to find it early and right. Deep models, mainly CNN, show great promise in making DR checks automatic. Yet, their success rests on having big and mixed sets of data, which might not be easy to have in local health spots. This work looks into making strong deep learning models for sorting DR using data from local places. We look at many CNN set-ups, use new ways to grow data, and use ways to adapt to different areas to make the model work better. We also use methods to make things clear, helping to trust AI more in eye checks. Our results show the hard parts and good points of using local data. They make clear how transfer learning and deep data work help cut down biases and boost how well models work. The plan we suggest tries to close the space between AI-based disease finding and real-world doctor use. It makes sure it works well for many different types of patients. La r´etinopathie diab´etique (RD) est l’une des principales causes de d´eficience visuelle dans le monde, n´ecessitant un diagnostic pr´ecoce et pr´ecis pour une intervention efficace. Les mod`eles d’apprentissage profond ont d´emontr´e un fort potentiel dans l’automatisation de la d´etection de la RD, mais leur robustesse d´epend largement de la disponibilit´e de vastes ensembles de donn´ees diversifi´es. Cette ´etude vise `a d´evelopper des mod`eles d’apprentissage profond robustes pour la classification de la RD en utilisant des ensembles de donn´ees locaux. Nous explorons diff´erentes architectures de r´eseaux de neurones convolutifs (CNN), des techniques d’augmentation des donn´ees et des strat´egies d’adaptation au domaine pour am´eliorer la g´en´eralisation du mod`ele. De plus, nous employons des m´ethodes d’explicabilit´e pour garantir l’interpr´etabilit´e et la fiabilit´e clinique des r´esultats. Nos analyses mettent en ´evidence les d´efis et les avantages li´es `a l’utilisation de donn´ees locales, en soulignant le rˆole du transfert d’apprentissage et des techniques avanc´ees de pr´etraitement dans la r´eduction des biais et l’am´elioration des performances du mod`ele. L’approche propos´ee vise `a combler l’´ecart entre la d´etection de la RD bas´ee sur l’IA et son application clinique, garantissant ainsi une fiabilit´e accrue sur des populations diverses.
Artificial Intelligence & Data Science
Keywords: Diabetic Retinopathy; Deep Learning; Convolutional Neural Networks; Transfer Learning; Explainability; Domain Adaptation; Medical Image Analysis.; R´etinopathie diab´etique; Apprentissage profond; R´eseaux de neurones convolutifs (CNN); Diagnostic pr´ecoce; Donn´ees locales; Explicabilit´e de l’IA